2005
DOI: 10.1161/01.hyp.0000160318.46725.46
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Selective Interaction Between Aging, Blood Pressure, and Sympathetic Nerve Activity

Abstract: Abstract-The mechanisms mediating the more striking age related increase in cardiovascular disease in women than in men are poorly understood. We tested the hypothesis that aging has a greater impact on sympathetic traffic in women than in men. Muscle sympathetic nerve activity (MSNA), blood pressure, and heart rate were measured in 120 healthy males and 96 healthy females aged 20 to 72 years. MSNA increased with age in both sexes, but age explained 53% of MSNA variance in female subjects and only 8% of MSNA v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
303
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(328 citation statements)
references
References 25 publications
18
303
3
4
Order By: Relevance
“…To this end, the present investigation examined sympathetic nervous system activation in healthy young and older adults using a standardized whole body skin surface cooling protocol via water-perfused suit (3,30,51,55). Consistent with a wide body of literature examining MSNA at rest in older adults at thermoneutrality (27,39,53), older adults in the present study exhibited increases in basal muscle sympathetic outflow. Furthermore, whole body cold stress elicited pronounced increases in MSNA burst frequency and strength in older, but not young, adults.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…To this end, the present investigation examined sympathetic nervous system activation in healthy young and older adults using a standardized whole body skin surface cooling protocol via water-perfused suit (3,30,51,55). Consistent with a wide body of literature examining MSNA at rest in older adults at thermoneutrality (27,39,53), older adults in the present study exhibited increases in basal muscle sympathetic outflow. Furthermore, whole body cold stress elicited pronounced increases in MSNA burst frequency and strength in older, but not young, adults.…”
Section: Discussionsupporting
confidence: 59%
“…MSNA and plasma norepinephrine concentrations are elevated with advancing age (15,24,27,39,53); therefore, impairments in norepinephrine-mediated vasoconstriction have generally been attributed to sustained agonist-mediated desensitization in ␣-adrenergic receptor responsiveness (24). Conversely, the age-related increase in MSNA during cooling may be a compensatory response as a result of age-associated reductions in ␣-adrenergic receptor responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, individual patients of the groups were Caucasians and were examined using the same protocol, under similar laboratory conditions, while avoiding the influence of age, dietary intake, body weight, large meal or visceral distension factors, which are known to affect sympathetic activity or its control. 14,15,17,19,[30][31][32][33][34] We also quantified the mean frequency of s-MSNA units and that of MSNA multiunits. The former was considered as an index of the mean frequency of efferent sympathetic nerve …”
Section: Discussionmentioning
confidence: 99%
“…4,14 On the other hand, previously reported findings in normotensive populations have not been consistent as to whether MSNA levels are different between men and women. Young women may have a lower [15][16][17][18][19] or similar 20,21 level of resting MSNA relative to young men. Also, older women may have a lower 15 or similar 17,19 level of resting MSNA relative to older men.…”
Section: Introductionmentioning
confidence: 99%
“…42-45 Also, older women have closer linkage between sympathetic nervous activity and BP than older men, and have exaggerated sympathetic nervous activity compared to their male counterparts. 43- 45 On the other hand, a previous study demonstrated that a 12-week exercise training program improved both the sympathetic and parasympathetic nervous activity in obese individuals. 46 In our study, it is possible that exercise training more greatly improved the exaggerated autonomic nervous activity in older females, and consequently led to their greater reduction of BP.…”
Section: Mechanisms Of Gender Differences In Bp Reduction In Responsementioning
confidence: 99%